(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
This review highlights the advantages of SR formulations, including reduced side effects, enhanced drug utilization, improved treatment efficacy, and better patient compliance. Key considerations for developing sustained release tablet involve the drug’s physicochemical properties and biological factors, such as absorption and metabolism. Various formulation strategies, including diffusion-controlled, dissolution-controlled, and osmotic systems, are discussed alongside essential evaluation parameters like density, hardness, and in-vitro drug release profiles. The outlook for sustained release tablets is bright , as their growing use in the pharmaceutical industry focuses on enhancing therapeutic effectiveness. Overall, sustained release tablet formulations represent a significant advancement in modern pharmacotherapy, enhancing efficacy and patient adherence to treatment regimens.